Study on the phase transition behaviors of thermoresponsive hyperbranched polyampholytes in water. (10th February 2016) - Tong, Jin-Ge; Wei, Zhong-Yu; Yang, Hao-Lin; Yang, Zhen-Yu; Chen, Yu
Abstract: The amino groups of hyperbranched polyethylenimine (HPEI) were partially modified with isobutyric anhydride to introduce isobutyramide (IBAm) groups to HPEI, resulting in an LCST-type thermoresponsive HPEI-IBAm that is positively-charged or neutral depending on the media pH. Succinic acid (SA) units were further introduced to HPEI-IBAm through acylation with succinic anhydride, resulting in the hyperbranched polyampholyte, HPEI-IBAm-SA, with both amino and carboxylic acid groups. 1 H NMR characterization proved the successful preparation of HPEI-IBAm-SA. Turbidimetry measurements showed that HPEI-IBAm-SA was also an LCST-type thermoresponsive polymer. The cloud point temperature ( T cp ) of HPEI-IBAm-SA was pH-dependent. Compared with the HPEI-IBAm precursor, HPEI-IBAm-SA showed the thermoresponsive property in a wider pH range. At isoelectric point, HPEI-IBAm-SA had the lowest T cp . The isoelectric point of HPEI-IBAm-SA could be tuned by controlling the amount of SA units, and the one with more SA units had a lower isoelectric point. Four halide anions with sodium as the counterion and four cations (Na +, K +, Mg 2+ and Ca 2+ ) with chloride as the counterion were used to measure the salt effects on the T cp of HPEI-IBAm-SA. The specific ranking orderings of these ions in reducing the T cp of HPEI-IBAm-SA were opposite at pH below and above isoelectric point. At pH above isoelectric point, the anion ranking is I − <Br − <Cl − <F −, and the cation ranking is Ca 2+ > Mg 2+ > Na + ≈ K + . At pH below isoelectric point, and, the anion ranking is F − ∼Cl − <Br − <I − in the low-salt-concentration region (≤10 −2 M), while the cation ranking is Na + ≈ K + > Mg 2+ ≈ Ca 2+ . All the specific salt ordering found in HPEI-IBAm-SA system could be also found in the system of the protein representative, ovalbumin, implying that HPEI-IBAm-SA was a better protein model to mimic the interactions among ions and proteins with a different isoelectric point. Graphical abstract: Highlights: Thermoresponsive hyperbranched polyampholytes were prepared. The T cp of hyperbranched polyampholytes was pH-dependent. Thermoresponsive hyperbranched polyampholyte was good protein model.